Clinical Case Studies in Home Health Care - Neal-Boylan, L. (Wiley Blackwell, 2013)
Home health care is an important aspect of community health and a growing area of healthcare services. Clinical Case Studies in Home Health Care uses a case-based approach to provide home healthcare professionals, educators, and students with a useful tool for thoughtful, holistic care. The book begins with a thorough and accessible introduction to the principles of home health care, including a discussion of supporting theoretical frameworks and information on managing complexities, transitioning patients to home care, and preparation for the home visit. Subsequent sections are comprised entirely of case studies organized by body system. Though cases are diverse in content, each is presented in a consistent manner, incorporating relevant data about the patient and caregivers and the approach to patient care and promoting a logical approach to patient presentation. Cases also include helpful tips about reimbursement practices, cultural competence, community resources, and rehabilitation needs. © 2011 by John Wiley & Sons, Inc.
Journal Abbreviation: Clin. Case Stud. in Home Health Care Pages: 485 Publication Title: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Multiple Sclerosis - Neal-Boylan, L. (Clinical Case Studies in Home Health Care, 2013)
Journal Abbreviation: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Theoretical Frameworks That Support Home Care - Neal-Boylan, L. (Clinical Case Studies in Home Health Care, 2013)
Journal Abbreviation: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Effectiveness of a role-modeling intervention on student nurse simulation competency - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2013)
Novice nurses are often inadequately prepared to respond to complex, patient care situations where patients' conditions deteriorate. Exposure to a video-taped intervention that role-models and reinforces expected behavior of an expert nurse before participation in a simulation may improve student nurse performance in a cost-effective manner. The primary purpose of this quasi-experimental pre-test, post-test study was to assess the preliminary effectiveness of a theory based role-modeling intervention on enhancing student nurse competency in responding to a simulated response to rescue event. Performance was measured by a previously validated Heart Failure Simulation Competency Evaluation Tool (c) (HFSCET). Total mean scores on the HFSCET for the pre-test (59.08) and post-test (87.08) were significantly different (p = .000); students performed better on the post-test after exposure to the role-modeling intervention. A power analysis indicated a large effect size (effect size = .926; alpha = 0.50; power = 0.991). Students who had a greater number of days between the intervention and the post-test had a lower score. This innovative intervention based on established learning theory may change the way educators prepare novice students to achieve expected clinical competencies in graded simulation performance assessments. (c) 2013 International Nursing Association for Clinical Simulation and Learning. Published by Elsevier Inc. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-811-864-193-208 tex.type: [object Object]
Keywords: Intervention; Nursing students; Performance assessment; Simulation; dept.nur